Penilaian Postur Kerja Operator Stasiun Sampling Point Dengan Metode Rapid Entire Body Assessment (REBA) dI PT. X - Bakar, Yusrizal (Jurnal Teknik Industri Terintegrasi (JUTIN), 2023)
This study aims to design a workplace improvement plan for Sampling Point operators at a CPO Processing Factory (PT.X) located in West Sumatra Province. This research started from the first stage by identifying all Musculoskeletal Disorder (MSDs) complaints in operators using the Nordic Body Map (NBM) method, then the second stage was carried out by assessing work posture using the Rapid Entire Body Assessment (REBA) method. This research found a condition that has the potential for musculoskeletal disorders (MSDs). Interviews were conducted with several operators, it can be concluded that almost every time they finish their work, they experience symptoms of muscle disorders. This is of course suspected because the operator’s work attitude is contrary to ergonomic principles. The final results of the assessment using the REBA (Rapid Entire Body Assessment) method conclude the following: Operators work in an attitude with a high level of risk category 3 which demands immediate corrective action and has an impact on musculoskeletal disorders. Then from the aspect of assessing the current work posture it is clear that the risk of musculoskeletal disorders is very high and requires immediate changes